Determination of Mineral Elements in the Fern Genus Pyrrosia Mirbel from Yunnan, China - Yang, Luhong; Zhang, Ji; Ding, Yongli; Wang, Yuanzhong; Lu, Shugang (Asian Journal of Chemistry, 2012)
The contents of nine mineral elements (Ca, Cr, Cu, Fe, K, Mg, Mn, Na and Zn) in nine species (Pyrrosia porvsa, Pyrrosia drakeana, Pyrrosia gralla, Pyrrosia lingua, Pyrrosia petiolosa, Pyrrosia subfurfuraceae, Pyrrosia calvata, Pyrrosia nudicaulis, Pyrrosia tonkiensis) of fern genus Pyrrosia Mirbel from Yunnan province of China were determined by atomic absorption spectrophotometry. Fern samples contained Ca (296.54-4033.32 μg g-1), Cr (183.58-326.49 μg g-1), Cu (15.07-75.21 μg g-1), Fe (53.66-548.58 μg g-1), K (7690.02-19459.30 μg g-1), Mg (1779.09-7423.35 μg g-1), Mn (4.60-394.32 μg g-1), Na (68.66-759.55 μg g-1) and Zn (14.68-93.08 μg g-1). The mineral element contents of fern genus Pyrrosia showed a wide variability among different species.